Prescriptiveness of the South African transfer pricing tax legislation in providing guidance on how to transact at an arm's length price - Manyaka, Puleng Owen (My University, 2011)
Transfer pricing is a significant taxation problem facing both tax authorities and multinational enterprises. Tax authorities around the world regulate transfer pricing through tax legislation, which requires that cross-border transactions within multinational enterprises be at arm’s-length. A number of countries in the international community have amended their transfer pricing tax legislation to be prescriptive by including regulations in their legislation on how to transact at arm’slength price. This research study presents an argument that the South African transfer pricing tax legislation is non-prescriptive as it does not have regulations on how to transact at arm’s-length price. With reference to the transfer pricing guidelines issued by the Organisation of Economic Development and Corporation and the experience of the United States of America in the enforcement of transfer pricing, this research study examines whether or not the South African transfer pricing tax legislation should be amended to be prescriptive by including regulations on how to transact at arm’slength price. The research findings reveal that to a certain extent the South African transfer pricing tax legislation is consistent with the transfer pricing guidelines issued by the Organisation of Economic Development and Corporation, but to a certain extent it is not. The research findings also reveal that non-prescriptive legislation has in the past created a problem in certain countries. Furthermore, the research findings reveal through an analysis of the United States of America’s transfer pricing enforcement experience, that prescriptive transfer pricing tax legislation in a tax system has a positive impact. Recommendation is therefore made in this research study that the South African transfer pricing tax legislation should be amended to be prescriptive by including regulations on how to transact at arm’s-length price. viii Keywords of the study: arm’s-length price, arm’s-length principle, income tax, IRS, multinational enterprise, non-prescriptive, OECD, Practice Note 7, prescriptive, SARS, section 31, section 482, South Africa, tax legislation, taxation, tax law, tax authority, transfer pricing, transfer pricing methods, United States of America.
Keywords: Transfer pricing; International business enterprises; Law and legislation; Taxation